DOES SERVICE INNOVATION IN TOURISM AND HOSPITALITY RELY MORE ON INTERNAL OR EXTERNAL FACTORS? - Lei, Ming; Chen, Chih-Hung (Journal of Economic Education, 2025)
Global tourism is projected to fully recover by 2024, presenting a significant opportunity for the tourism and hospitality industry worldwide. However, companies in this sector continue to face challenges such as a turbulent external environment, high competitiveness, and a lack of confidence in the industry’s recovery. To address these challenges, companies must focus on service innovation and improving their service innovation performance (SIP). Exploring SIP at the individual level is crucial because individual innovation is the foundation of organizational SIP. Based on the resource-based view (RBV), the knowledge-based view (KBV) and contingency theory, this study constructs the research paradigm of "internal and external innovation environment-individual capability-innovation performance" and puts forward the conceptual model of this study. This study aims to clarify the influence mechanism of internal and external innovation environment factors on service innovation performance at the individual level. A total of 417 questionnaires were collected for analysis from middle and senior management employees of star hotels in China. The results showed that there are direct and indirect effects on both paths of knowledge sharing and technology turbulence and SIP, with information literacy playing a mediating role; Furthermore, the study suggests that market turbulence has a positive moderating effect on the relationship between technology turbulence and information literacy. These findings have both practical and theoretical implications.